Cluster headache: understandings of current knowledge and directions for whole process management - Xu, Xiao-Hu; Li, Yi-Ming; Ren, Li-Na; Xu, Xiao-Fan; Dai, Yi-Long; Jin, Cheng-Qiang; Yang, Rui-Rui (Frontiers in Neurology, 2024)
Cluster headache (CH) is a common primary headache that severely impacts patients' quality of life, characterized by recurrent, severe, unilateral headaches often centered around the eyes, temples, or forehead. Distinguishing CH from other headache disorders is challenging, and its pathogenesis remains unclear. Notably, patients with CH often experience high levels of depression and suicidal tendencies, necessitating increased clinical attention. This comprehensive assessment combines various reports and the latest scientific literature to evaluate the current state of CH research. It covers epidemiology, population characteristics, predisposing factors, and treatment strategies. Additionally, we provide strategic insights into the holistic management of CH, which involves continuous, individualized care throughout the prevention, treatment, and rehabilitation stages. Recent advances in the field have revealed new insights into the pathophysiology of CH. While these findings are still evolving, they offer a more detailed understanding of the neurobiological mechanisms underlying this disorder. This growing body of knowledge, alongside ongoing research efforts, promises to lead to the development of more targeted and effective treatments in the future.